Analisis Penerapan Akuntansi Syariah Berdasarkan PSAK Tentang Pembiayaan Musyarakah Nomor.406 Di BMT Fajar Bina Sejahtera Metro - Faizah, Fellita Nur; Yudistira, Era; Nisa, Thoyibatun; Swandini, Witantri Dwi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study discusses the application of sharia accounting to musyarakah financing based on PSAK 406, in order to assess its compliance with applicable standards and identify the obstacles faced by BMT Fajar Bina Sejahtera Metro in implementing musyarakah financing contracts. The practice of musyarakah financing in BMT often faces obstacles related to capital recording, profit sharing ratio allocation, and financial reporting processes. Although PSAK 406 serves as a guide, its implementation is not always optimal. This study aims to initiate the implementation of sharia accounting in musyarakah financing in accordance with PSAK 406, assess compliance with established standards, and identify the challenges faced by BMT Fajar Bina Sejahtera Metro in implementing musyarakah financing contracts. This approach uses data collected through surveys and direct interviews with BMT, which is sometimes referred to as a qualitative descriptive method. The research findings indicate that BMT Fajar Bina Sejahtera Metro fails to implement musyarakah financing accounting practices that are in line with sharia standards. After analysis, the researcher concluded that BMT Fajar Bina Sejahtera Metro has not sufficiently complied with PSAK No. 406 in its application of musyarakah financing accounting practices. This lack of compliance is particularly relevant to the recognition, measurement, presentation, and disclosure of transactions as a passive partner, which could facilitate fraudulent activities. Consequently, the inaccurate determination of capital and loss sharing is hampered by limited customer interest and understanding of the complex musyarakah mechanism, as well as operational procedures and recording techniques that lack transparency and fail to meet established standards.